Integral Manufacturing of Plastic-Metal Hybrids Consisting of Endless Fiber Reinforcement Using Injection Molding. (2019) - Gebken, Tobias; Kühn, Markus; Demes, Michael; Müller, Anke; Dröder, Klaus
Abstract: Injection molding is an economically attractive manufacturing process of short and long fiber-reinforced thermoplastic (TFRP) parts. In structural applications, the fiber specifications, volume content, length, material and orientation are influencing the characteristics of strength, stiffness and brittleness. Due to a nearly isotropic material behaviour of short TFRP parts, directional long or endless TFRP are suitable for a load path-oriented design with an improved stiffness and strength. This paper deals with the integration of endless fibers in the injection molding process, focussing on the reinforced interface between metal and thermoplastic parts. The hybridization process and a calculation of the fiber infiltration time are present topics. Furthermore, the performance of fiber-reinforced interfaces between metal and thermoplastic parts is characterized in tensile tests.